Հովհաննես Բրգութենցի գանձերն ու տաղերը - Թումանյան, Լուսինե (Մատենադարան)
The article contains the first publication of the gandzs (litanies) and taghs (odes) of the famous Archimandrite Yovhannēs Brgut‘ents‘, which we have found in manuscripts. They are dedicated to the Church of Aght‘amar island and Apostle Thomas. We found information that one of the manuscripts taken from the Narek Monastery to Aght‘amar contained Yovhannēs’s litanies. According to another source, another manuscript kept in Aght‘amar contained a gandz and a tagh of the same author. We tried to find these manuscripts. There is a manuscript, written in 1440 in Vostan, which Ghevond P‘irghalemyan saw in the Narek Monastery in 1866. It was taken to the Aght‘amar Monastery, and in 1915–1916, during the Genocide, it was rescued and brought to Holy Ēchmiadzin. Now it is Ms M5404. In the 17th century, the gandz of Yovhannēs Brgut‘ents‘ dedicated to Apostle Thomas was written on the last pages of this manuscript. As for the manuscript that Archimandrite Ghevond saw in Aght‘amar in 1602, it is certainly the same manuscript written by T‘uma Minasenets‘ in 1445 in Aght‘amar (M5521). In 1602, the gandz and the tagh of Yovhannēs Brgut‘ents‘ dedicated to the Church of Surb Khach (Holy Cross) in Aght‘amar were added on the last pages of this manuscript. В статье впервые публикуются обнаруженные нами гандзы (церковные песнопения) и таги (оды) известного архимандрита Ованеса Бргутенца, посвященные церкви на острове Ахтамар и апостолу Фоме. До нас дошли сведения, что одна рукопись, вывезенная из Нарекского монастыря в Ахтамар, содержит песни Ованеса Бргутенца. Согласно другому источнику, в другой рукописи, хранящейся в Ахтамаре, содержится гандз и таг Ованеса Бргутенца. Мы попытались найти эти рукописи. Есть рукопись, написанная в 1440 году в Востане, которую Гевонд Пиргалемян видел в Нарекском монастыре в 1866 году. Спустя годы она была перевезена в Ахтамарский монастырь. В 1915-1916 гг., во времая Геноцида, рукопись была спасена и перевезена в Святой Эчмиадзин, а сейчас находится в Матенадаране имени Месропа Маштоца (М 5404). На последних страницах этой рукописи в XVII веке был написан гандз Ованеса Бргутенца, посвященная апостолу Фоме. Что касается рукописи, которую архимандрид Гевонд видел в Ахтамаре в 1602 году, мы уверены, что это та самая рукопись, которую Тума Минасенц скопировал в 1445 году в Ахтамаре (MM 5521). В 1602 г. на последних страницах этой рукописи были добавлены гандз и таг Ованеса Бргутенца, посвященные церкви Сурб Хач (Святой Крест) на острове Ахтамар.
Keywords: Ձեռագիր; Տաղեր